2019
DOI: 10.1093/ajcn/nqz161
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of supplemental EPA and DHA on the omega-3 index

Abstract: Background Supplemental long-chain omega-3 (n–3) fatty acids (EPA and DHA) raise erythrocyte EPA + DHA [omega-3 index (O3I)] concentrations, but the magnitude or variability of this effect is unclear. Objective The purpose of this study was to model the effects of supplemental EPA + DHA on the O3I. Methods Deidentified data from 1422 individuals from 14 publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 48 publications
6
61
2
Order By: Relevance
“…The calculated red cell bioavailability of EPA and DHA from the omega-3-PUFA enriched chicken-meat and eggs was 1.4% per 100 mg/day of EPA and DHA. This appears to equal or exceed that previously recorded for oily fish (0.6-0.8%), and fish oil supplements (0.2-0.6%) 35,36 . Furthermore, adherence to the allocated diets within the study was excellent, and compares favorably with other lifestyle and pharmacological strategies for the primary prevention of cardiovascular events 37 .…”
Section: Discussioncontrasting
confidence: 58%
“…The calculated red cell bioavailability of EPA and DHA from the omega-3-PUFA enriched chicken-meat and eggs was 1.4% per 100 mg/day of EPA and DHA. This appears to equal or exceed that previously recorded for oily fish (0.6-0.8%), and fish oil supplements (0.2-0.6%) 35,36 . Furthermore, adherence to the allocated diets within the study was excellent, and compares favorably with other lifestyle and pharmacological strategies for the primary prevention of cardiovascular events 37 .…”
Section: Discussioncontrasting
confidence: 58%
“…Providing sufficient levels of ω-3 supplementation is paramount to achieving ω-3 HUFA levels capable of reducing symptoms involved in lupus flares. A recent study presented an equation to predict the change in the O3I using the baseline O3I and the supplemented dose of EPA and DHA (104). These findings suggested that individuals with a baseline O3I around 4%, a level typical for many individuals consuming a Western diet, would require 1,500 mg/day EPA + DHA for 13 weeks to achieve an O3I of 8%.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ALA, which can constitute up to 50% of silkworm pupa oil content, is a ω ‐3 polyunsaturated fatty acid (PUFA). It is a precursor to eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), both of which have vital physiological roles in human brain development, cardiovascular health, and inflammatory responses . α ‐Linolenic acid is widely used in the medical field for the prevention and treatment of multiple diseases, and in the food industry as a nutritious additive in foods and beverages.…”
Section: Introductionmentioning
confidence: 99%